Simultaneous Estimation of Quercetin and Silymarin Method Development and Validation - Ashish Baldi, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Simultaneous Estimation of Quercetin and Silymarin Method Development and Validation